2014
DOI: 10.1002/ps.3754
|View full text |Cite
|
Sign up to set email alerts
|

EPSPS amplification in glyphosate‐resistant spiny amaranth (Amaranthus spinosus): a case of gene transfer via interspecific hybridization from glyphosate‐resistant Palmer amaranth (Amaranthus palmeri)

Abstract: Glyphosate resistance in A. spinosus is caused by amplification of the EPSPS gene. Evidence suggests that part of the EPSPS amplicon from resistant A. palmeri is present in glyphosate-resistant A. spinosus. This is likely due to a hybridization event between A. spinosus and glyphosate-resistant A. palmeri somewhere in the lineage of the glyphosate-resistant A. spinosus plants. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 21 publications
3
105
0
5
Order By: Relevance
“…6D), which may suggest a different mechanism of EPSPS gene amplification. Interspecific hybridization between different amaranth species is possible (reviewed by Sellers et al, 2003;Ward et al, 2013), and several cases of herbicide resistance transfer via gene flow were reported, including resistance to imazethapyr (an ALS inhibitor) was transferred from A. tuberculatus to A. palmeri, and glyphosate resistance was transferred from A. palmeri to other Amaranthus species including spiny amaranth (A. spinosus), smooth pigweed (A. hybridus) and A. tuberculatus (Wetzel et al, 1999;Gaines et al, 2012;Nandula et al, 2014). A random distribution of amplified EPSPS copies throughout the chromosomes was reported for A. palmeri (Gaines et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6D), which may suggest a different mechanism of EPSPS gene amplification. Interspecific hybridization between different amaranth species is possible (reviewed by Sellers et al, 2003;Ward et al, 2013), and several cases of herbicide resistance transfer via gene flow were reported, including resistance to imazethapyr (an ALS inhibitor) was transferred from A. tuberculatus to A. palmeri, and glyphosate resistance was transferred from A. palmeri to other Amaranthus species including spiny amaranth (A. spinosus), smooth pigweed (A. hybridus) and A. tuberculatus (Wetzel et al, 1999;Gaines et al, 2012;Nandula et al, 2014). A random distribution of amplified EPSPS copies throughout the chromosomes was reported for A. palmeri (Gaines et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the EPSPS gene and mRNA sequences of A. palmeri and A. tuberculatus available in public databases, including EPSPS sequence from GR A. palmeri (Gaines et al, 2013) we selected A. palmeri specific primers AW 190 and AW155 amplifying a 697-bp fragment from EPSPS intron1 as reported earlier (Nandula et al, 2014) and developed two additional markers. PCR with primers M1a and M19 was expected to amplify 235-and 103-bp fragments from EPSPS exons 2 and 5, respectively, each with a single nucleotide polymorphism (SNP) between the two species.…”
Section: Molecular Marker Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the biotypes cited in Argentina, ALS inhibitor herbicides resistance is due to site-specific mutation [8]. Glyphosate resistance mechanism is still unknown, but in a biotype of A. palmeri in USA, gene amplification was proven to be the cause [9,10]. However, a rapid quantification of shikimic acid accumulation can be measured in glyphosate-resistant biotypes [11].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, waterhemp and Palmer amaranth (A. palmeri) have evolved resistance to glyphosate (Heap, 2015). Because of the importance of glyphosate to current weed management, there is concern that this resistance will be transferred to other Amaranthus species (Culpepper et al, 2006;Nandula et al, 2014).…”
Section: Introductionmentioning
confidence: 99%